2015
DOI: 10.1371/journal.pone.0145664
|View full text |Cite
|
Sign up to set email alerts
|

Judged and Remembered Trustworthiness of Faces Is Enhanced by Experiencing Multisensory Synchrony and Asynchrony in the Right Order

Abstract: This work builds on the enfacement effect. This effect occurs when experiencing a rhythmic stimulation on one’s cheek while seeing someone else’s face being touched in a synchronous way. This typically leads to cognitive and social-cognitive effects similar to self-other merging. In two studies, we demonstrate that this multisensory stimulation can change the evaluation of the other’s face. In the first study, participants judged the stranger’s face and similar faces as being more trustworthy after synchrony, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
(59 reference statements)
3
7
0
Order By: Relevance
“…Even though we did not predict this order effect, similar results can be found in previous research (e.g., Tajadura-Jiménez, Lorusso, & Tsakiris, 2013; Toscano & Schubert, 2015). For instance, Toscano and Schubert found that the extent to which a person judges another person’s face as more or less trustworthy as a function of synchrony only changed when the synchronous stimulus occurred before the asynchronous one.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Even though we did not predict this order effect, similar results can be found in previous research (e.g., Tajadura-Jiménez, Lorusso, & Tsakiris, 2013; Toscano & Schubert, 2015). For instance, Toscano and Schubert found that the extent to which a person judges another person’s face as more or less trustworthy as a function of synchrony only changed when the synchronous stimulus occurred before the asynchronous one.…”
Section: Discussionsupporting
confidence: 79%
“…Method Procedure Participants were informed that this was a study on how humans form impressions about others' capacity to start and manage a business. They saw two videos (from Schubert, Toscano, & Waldzus, 2016;Toscano & Schubert, 2015) showing two women walking side-by-side facing forward. Each video lasted approximately 19 s. In order to ensure that movement alone accounted for any differences in participants' responses, the videos were muted, actors did not move their lips, and they kept their facial expressions as neutral as possible.…”
Section: Studymentioning
confidence: 99%
“…Sometimes, assessments of trustworthiness derive from an elaborate evaluation of the risks involved and the extent to which possible benefits outweigh potential losses [4,5]. Often, trust is intuitive, affect-based and reflecting a 'gut feeling' based on the partner's physical features [6][7][8][9][10]. Across species, such 'gut feeling' may derive from a variety of sources, such as partners' bodily scents (in rodents [11,12]; in humans [13]), posture (in rodents [14]; in humans [15,16,17,18]) and emotional vocalizations (in rodents [19]; in chimpanzees [20]; in humans [21]).…”
Section: Introductionmentioning
confidence: 99%
“…Condition sequence. Considering the possible dependency of trust on the sequence of conditions (Toscano & Schubert, 2015), we also ran analyses of variance (ANOVAs) with synchrony and sequence (synchronous before asynchronous, N = 23, vs asynchronous before synchronous, N = 22) on all measures. No significant interaction effect was found, all effects ps > .10.…”
Section: Resultsmentioning
confidence: 99%